Big brother at work [workplace surveillance]. - Kushner, D. (IEEE spectrum)
Newer technologies are allowing employers to keep tabs on workers as never before. These tactics range from radiofrequency identification (RFID) tags to GPS chips embedded in cellphones and company cars. Even video surveillance is being reborn, with searchable digital systems that can run over a network. Part of the reason for employer surveillance is because there are only a few laws protecting privacy at work, particularly in the US. While there are certain standards for privacy in one's own home, those rights generally don't extend to the workplace. To guard against invasion of privacy, employees are advised not to send personal email from work and to find out whether and how their companies monitor their workplace. To make it more difficult to track employee Web surfing, a USB thumb drive, called the StealthSurfer, is available. The StealthSurfer features self-contained browser that caches the files and cookies accrue while surfing.